The Manifestation of Campbell's Law: Consequences of Eliminating of Social Studies From the Curriculum. Issue 1 (2nd January 2018) - Byrd, Marie; Varga, Bretton A.
ABSTRACT: The manifestation of Campbell's Law is examined in light of the current era in American public schools of high stakes testing inclusive of narrowed curriculums and teaching to the test. The decades-long practice of reducing instructional time of non-tested subjects, which includes social studies fundamentals, has resulted in a less informed citizenry. Social studies instruction promotes citizens who are able to make informed decisions that are inclusive of differentiating between facts, generalizations, and opinions without bias. The construction of individual viewpoints through a narrow lens without discrimination between opinions and historical facts is of concern today as Americans form opinions regarding controversial social issues and engage in social activism.